Exploring Cultural Significance: How Do “Child” Metaphors Differ Between Indonesian and English? - Rahim, Niswa Binti (Applied Linguistics: Innovative Approaches and Emerging Trends, 2024)
This study aims to compare the usage of metaphors containing the term “anak” or “child” in both Indonesian and English. Analyzing data from various textual sources, prevalent metaphors in both languages were identified. Despite some similarities, significant differences exist in their usage and interpretation. Examples include “Anak Buah/Subordinate”, “Anak Lokal/Native”, “Anak Panah/arrow, “Anak Perusahaan/subsidiary company”, “Suku Anak Dalam/tribal people”, Anak Sumpit/Arrowhead Archery, and “Anak Tangga/Staircase.” These metaphors are deeply ingrained not only in linguistic structures but also in the collective values, beliefs, and experiences of the societies where the languages are spoken. Indonesian metaphors often reflect cultural values like unity and interaction with nature, while English metaphors may portray individualism or technology. Understanding these cultural distinctions is crucial for effective cross-cultural communication.